2006
DOI: 10.1080/00016480500312554
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological parameters of recurrence and malignant transformation in sinonasal inverted papilloma

Abstract: Malignancy was related to the presence of bone invasion (p=0.039), the absence of inflammatory polyp (p=0.033), increase in the ratio neoplastic epithelium:stroma (p=0.037), increase in hyperkeratosis (p=0.030), the presence of squamous epithelial hyperplasia (p=0.044), increase in the mitotic index (p=0.029) and a decrease in the number of eosinophils (p=0.037). Multiple recurrences (without malignancy) were related to frontal sinus origin (p=0.042), increase in hyperkeratosis (p=0.041), the presence of squam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 10 publications
2
59
0
8
Order By: Relevance
“…Malignancy was associated with the presence of bone invasion, absence of inflammatory polyps, high ratio of neoplastic epithelium to stroma, increased hyperkeratosis and decreased eosinophils. Clinically benign behaviour was related to the presence of inflammatory polyp and absence of hyperkeratosis [7] (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malignancy was associated with the presence of bone invasion, absence of inflammatory polyps, high ratio of neoplastic epithelium to stroma, increased hyperkeratosis and decreased eosinophils. Clinically benign behaviour was related to the presence of inflammatory polyp and absence of hyperkeratosis [7] (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…Eggers et al [6] reported a retrospective analysis of 93 cases and Katori et al [7] analysed a series of 39 cases of inverted papilloma to establish histological parameters to predict recurrence and malignant transformation. Multiple recurrences without malignancy were related to frontal sinus site, increased hyperkeratosis, presence of squamous epithelial hyperplasia, and increased mitotic index.…”
Section: Discussionmentioning
confidence: 99%
“…2,10 Several factors have been shown to increase the risk of recurrence for IP including tobacco exposure, increased tumor size, increased hyperkeratosis, squamous epithelial hyperplasia, increased number of mitoses, bilaterality, and the lack of inflammatory polyps. 1,9,[27][28][29] In addition, IP originating from the frontal sinus tend to have multiple recurrences, likely because of technical difficulties operating in this location. 9,28 Most recurrences usually occur within the first 3 years, although recurrences 10 years postoperatively have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…1,9,[27][28][29] In addition, IP originating from the frontal sinus tend to have multiple recurrences, likely because of technical difficulties operating in this location. 9,28 Most recurrences usually occur within the first 3 years, although recurrences 10 years postoperatively have been reported. 9,23 Long-term follow-up is recommended given that recurrences can occur after prolonged periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…[20] Human papilloma virüsün varlığı ve p53 aşırı ekspresyonu inverted papillomda malign dönü-şümün göstergesi olabilir. [21] Ancak p53 aşırı ekspresyonunun genellikle HPV negatif olgularda görüldüğü belirtilmiştir. [22] Sonuç olarak, inverted papillom, tek taraflı nazal polipozise benzer semptomlar veren, benign bir tümör-dür.…”
Section: şEkil 2 Stromada Hafif Lenfositik Infiltrasyon Izlenmektediunclassified